Analisis Algoritma Regresi Linear Sederhana dalam Memprediksi Tingkat Penjualan Album KPOP - Silvia Lestari (INSOLOGI: Jurnal Sains dan Teknologi, 2023)
Music albums in the current era of globalization are quite sought after by their fans, not only by young people, but fans are starting to reach all walks of life, from children, young people and even adults who also buy albums for their own pleasure and hobby needs. In this study, researchers tried to dig up information about music album sales, especially Korean album sales, which are currently on the rise and are enjoyed by many people, namely NCT127. Which is where NCT127 itself is one of the music groups from the country of Gineng, namely South Korea, which recently held a concert in Jakarta which had an extraordinary effect. So from that the researchers tried to analyze the level of sales of nct127 music albums by using the estimation algorithm in data mining. namely Linear Regression to find out and predict the level of Korean album sales by looking for the values ​​of X, Y, X2, Y2, XY which is done by looking for the coefficient values ​​and the dependent variable of each attribute or label.